2022
DOI: 10.1186/s12987-022-00334-y
|View full text |Cite
|
Sign up to set email alerts
|

Polarized α-synuclein trafficking and transcytosis across brain endothelial cells via Rab7-decorated carriers

Abstract: Parkinson’s disease is mainly caused by aggregation of α-synuclein (α-syn) in the brain. Exchange of α-syn between the brain and peripheral tissues could have important pathophysiological and therapeutic implications, but the trafficking mechanism of α-syn across the blood brain-barrier (BBB) remains unclear. In this study, we therefore investigated uptake and transport mechanisms of α-syn monomers and oligomers across an in vitro BBB model system. Both α-syn monomers and oligomers were internalized by primary… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…This correlates well with dSTORM imaging by Aartsma and co-workers which showed that α-syn amyloid aggregates localize with endocytotic vesicles . It has also been shown that α-syn monomers colocalize with markers for late endosome/lysozyme Rab7 and the retromer protein VPS35 in brain endothelial cells after uptake from media . Furthermore, mitochondrial fragmentation has been observed in a PD disease mouse model with a heterozygous (D620N) mutation of Vacuolar Protein Sorting 35 (VPS35) .…”
Section: Resultssupporting
confidence: 85%
“…This correlates well with dSTORM imaging by Aartsma and co-workers which showed that α-syn amyloid aggregates localize with endocytotic vesicles . It has also been shown that α-syn monomers colocalize with markers for late endosome/lysozyme Rab7 and the retromer protein VPS35 in brain endothelial cells after uptake from media . Furthermore, mitochondrial fragmentation has been observed in a PD disease mouse model with a heterozygous (D620N) mutation of Vacuolar Protein Sorting 35 (VPS35) .…”
Section: Resultssupporting
confidence: 85%
“…This has limited previous investigations and could potentially also explain the contradictory findings of the protein and lipid distributions in apicobasal cell polarity in general [ 9 , 11 , 42 ]. Here, we examined the apicobasal polarity of TfR in the established BBB model, which previously exhibited polarized alpha-synuclein transport [ 43 ], and has been reported to provide influx and efflux transport, depending on the specific compound [ 44 , 45 ]. To further validate the model, we examined the polarized transport of R123, a substrate for the transporter P-gp [ 35 , 46 ], and considered an efflux transporter in BECs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, α-synuclein can cross the BBB in both directions, and α-synuclein can inhibit Aβ efflux in an LRP1-dependent manner (Sui et al, 2014). However, the polarized α-synuclein trafficking across BECs in the luminal-abluminal direction is directed by Rab7/VPS35 trafficking pathway, which is different from the Rab11-directed Aβ transcytosis in BECs (Alam et al, 2022). In addition, systemic inflammation promotes the α-synucleincontaining red blood cell (RBC)-derived extracellular vesicles (EVs) across BBB (Matsumoto et al, 2017).…”
Section: Dysregulation Of Bec Transportsmentioning
confidence: 98%